Taxonomia do gênero Senna Mill. (Leguminosae-Caesalpinioideae) no estado do Ceará, Brasil - Nascimento, Hugo Pereira do (2023)
Leguminosae is a monophyletic family with a cosmopolitan distribution, present in human cultures due to its significant economic potential. It's the third largest family of Angiosperms, comprising about 765 genera and 19,500 species. Within this family, the pantropical genus Senna Mill. is a monophyletic taxon belonging to the subfamily Caesalpinioideae, which includes approximately 350 species. In Brazil, Senna is represented by around 80 species, while in the Northeast region, there are 54 species. For the state of Ceará, there were only studies on Senna populations occurring in the Caatinga and the Baturité. Thus, studies on the taxonomy and distribution of the genus for the entire state were lacking. The objective of this study was to conduct a floristic survey and morphological description of the Senna genus for the state of Ceará. Exsiccates deposited in herbaria were analyzed, as well as field work carried out between 2022 and 2023. In Ceará, Senna is represented by 21 species, with six of them being endemic to Brazil. Senna cana is a new occurrence in the state, recorded in the Crato region. Among the studied species, 15 are classified as Least Concern on the IUCN Red List of Threatened Species, and 20 species are found in conservation units. The information in this manuscript enables the identification and discussion of Senna representatives occurring in the state, through morphological descriptions, an identification key, taxonomic comments, illustrations, photographs, maps, distribution data, and phenologies. This studie assists in the development of future projects involving the conservation and biodiversity of Senna, while also expanding information about the group both for the Northeast region and at the national scope.